Engineering Digital Transformation Proceedings of the 11th International Conference on Industrial Engineering and Industrial Management - Ortiz, Ángel; Andrés Romano, Carlos; Poler, Raul.; García-Sabater, José-Pedro.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book outlining the latest developments in engineering digital transformation gathers a selection of the best papers presented at the 11th International Conference on Industrial Engineering and Industrial Management (CIO 2017), held in Valencia, Spain, from July 5th to 6th, 2017. The papers discuss topics in the following areas: strategy and entrepreneurship, OR, modelling and simulation, production, logistics and supply chain management, information systems, quality and product management, knowledge and project management, service systems, and education.
Chapter 1. New Perspective on Building Strategy in Public Education Institution -- Chapter 2. Role Clarity and Satisfaction for Knowledge Workers -- Chapter 3. An Innovation Model for EPC/Turnkey Sector: the Case of Abengoa Solar New Technologies -- Chapter 4. How Does Working on University-Business Collaborative Projects Foster the Industrial Doctorates´ Learning Process? -- Chapter 5. Business Model Innovation from a Technology Perspective: A Review -- Chapter 6. The Impact of Real Estate Taxations on the Iinter-Municipal Migration Which Influences The Housing Construction Dynamics -- Chapter 7. Developing a Pre-scale for Evaluating Supervisors´ Directive Style in Continuous Improvement Environments -- Chapter 8. Mandatory Convertible Bonds as an Efficient Method of Issuing Capital -- Chapter 9. Culture and Environment as Antecedents of Technological Entrepreneurship -- Chapter 10. Drivers´ Perception of the Major Advantages of Electric Vehicles -- Chapter 11. A Study on Consumer Behaviour inthe Sharing Economy -- Chapter 12. Levels of Application of Public R&D&I Policy Models -- Chapter 13. Limitations and Pitfalls of the Brain that Prevent us from Thinking -- Chapter 14. Lessons Learned in Assessment of Technology Maturity -- Chapter 15. Assessing Worldwide Research About Performance Measurement for SMEs: 2006 - 2016 -- Chapter 16. Organizational Structures in Small and Medium-sized Enterprises (SMEs) and their Performance Measurement Systems -- Chapter 17. Resilience Engineering: Concepts of the New Paradigm -- Chapter 18. The Importance of Intangible Liabilities to Business Management etc.
Keywords: Industrial engineering; Production engineering; Production management; Computer simulation; Industrial and Production Engineering; Operations Management; Computer Modelling